2005
DOI: 10.1007/s00204-005-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the theta class GST isozyme, YdfYdf, in low GST dogs

Abstract: We have reported the existence of low glutathione S-transferase (GST) dogs whose GST activity to 1,2-dichloro-4-nitrobenzene (DCNB) as a substrate (GST-D activity) is quite low, and have also reported significant individual differences in dog liver GST-D activity. The dogs were classified as "low", "middle", or "high" GST dogs based on their GST-D activity. In the present study, in order to investigate the causes of quite low GST-D activity in low GST dogs and the individual differences in dog GST-D activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The overall MAF for GSTT5 385_390delGACCAG was 0.144 in our sample of 45 livers, and was significantly higher (0.444) in a small subpopulation of purpose‐bred laboratory beagles, with 2 of 9 (22%) beagles being homozygous. This observation is consistent with the previous finding of low DCNB activities in 12% of research colony beagles . Our study was limited by a relatively low number of individual dog livers available, many of which were from purpose‐bred or mixed‐breed dogs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The overall MAF for GSTT5 385_390delGACCAG was 0.144 in our sample of 45 livers, and was significantly higher (0.444) in a small subpopulation of purpose‐bred laboratory beagles, with 2 of 9 (22%) beagles being homozygous. This observation is consistent with the previous finding of low DCNB activities in 12% of research colony beagles . Our study was limited by a relatively low number of individual dog livers available, many of which were from purpose‐bred or mixed‐breed dogs.…”
Section: Discussionsupporting
confidence: 93%
“…Polymorphisms in genes that encode GST enzymes are important in the epidemiology of cancer risk in humans, but little is known about GST variants in dogs. Previous studies had found polymorphic activity for the GST‐theta substrate, DCNB, in beagle dog livers, with some dogs having virtually no activity . These latter dogs were reportedly missing a GST‐theta protein with an N‐terminal amino acid sequence, MPPELFLDLYSPPPRAIYIFALKNGIP, which we matched to a novel canine GST gene on chromosome 26.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Epidemiologic studies have found significant associations between canine lymphoma and exposure to industrial pollutants, solvents and herbicides, but the role of specific environmental carcinogens in the development of lymphoma in dogs is not clear . GSTT1 activities have been characterized in livers from research beagles, and 12% of these dogs had virtually no GSTT1 protein expression or activity . However, the genetic basis for this variability, and its toxicological consequences, has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…We chose GST‐theta variants for this study because of marked variability in GST‐theta activities in dogs and functionally defective canine GST‐theta alleles . However, CP response in humans can be influenced by other GST gene variants, alone or in combination .…”
Section: Discussionmentioning
confidence: 99%